0 like 0 dislike
0 like 0 dislike
Really need help transposing this simple question.

1 Answer

0 like 0 dislike
0 like 0 dislike
so `((a+b)cd) / e = f`?

( (a+b)(c)(d) ) / e = f
  multiply by e:
( (a+b)cde ) / e = ef
(a+b)cd = ef
  divide by (a+b)c:
( (a+b)cd)) / (a+b)c  = ef/((a+b)c)
d = ef / ((a+b)c)

the brackets and fraction make it a little more intimidating, but you're still using the same algebra to move variables around. with practice it will become easier to see what steps you need to take to isolate the variable you want!

No related questions found

33.4k questions

135k answers


33.7k users

OhhAskMe is a math solving hub where high school and university students ask and answer loads of math questions, discuss the latest in math, and share their knowledge. It’s 100% free!